A case report of Anisakis pegreffii (Nematoda, Anisakidae) identified from archival paraffin sections of a Croatian patient. Issue 1 (December 2015) - Mladineo, Ivona; Popović, Marijana; Drmić-Hofman, Irena; Poljak, Vedran
Abstract Background This is the first report of anisakiasis in a Croatian patient, evidenced from an archival paraffin-embedded and hematoxylin-eosin stained tissue section. Anisakiasis has been only suspected in the country based on previously detected anti-Anisakis IgE seroprevalence in the healthy coastal population, as well as an acute case where pathohistological and serological findings suggested the diseases, but the migrating larva has not been retrieved. Case presentation Seventy years-old female, operated in 1998 for pulmonary carcinoma, was admitted to the General hospital Šibenik, Croatia in 2003, because of gastric pain and nausea that lasted for couple of days. She was showing good general condition, full mobility and lucidity, subfebrile status. Abdominal palpation inferred acute pain in paraumbilical and ileocecal region. Exploratory right pararectal laparotomy revealed a hardened, 5 cm-long structure, located intraluminally in the sigmoid colon, not perforating colon serosa. The process has been dissected and sent for patohistological diagnosis. Results showed a 2 mm-long whitish nematode spiralised in muscular layer of colon mucosa surrounded by granulomatous inflammation. Conclusion After genomic DNA isolation of the nematode from the histological section, and amplification at the mitochondrial cytochrome oxidase 2 locus, etiological agent has been identified asAnisakis pegreffii . Used methodology suggests that screening of archival suspicious sections is feasible in order to study epidemiology of this zoonotic disease poorly recognised in Croatia.